Contemporary discourses on the possibility of an 'Islamic state': an overview. Issue 3 (2nd July 2016) - Ahmad Dar, Showkat
ABSTRACT: The surprising rise of the Islamic State of Iraq and Sham (ISIS) and its proclamation as the caliphate on 29 June 2014 imposed an obvious threat to nation-states. The continuous controversy over the nature and applicability of Islamic tenets to governmental institutions has yet to be solved. The possibility and impossibility of an Islamic state in contemporary times is observed by analyzing the very nature of Islam. The concept of an Islamic state is based on the teachings of the Koran and Sunnah, as meant for human welfare and happiness that, according to Muhammad Asad, would automatically preclude the government of such a state from contemplating wars of aggression. This article attempts to analyze the political developments that have taken place since the beginning of the twentieth century and the failure of the Muslims in establishing an Islamic state, despite upholding sharī'ah principles.